Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
nam tran
Xem chi tiết
tam mai
13 tháng 7 2019 lúc 22:05

a) -1/4

b)10/11(-8/9+7/18)=10/11.(-1/2)=-5/11

c) 3/14.28-13/21.28+29/42.28-8=28(3/14-13/21+29/42)-8=28.2/7-8=8-8=0

nam tran
Xem chi tiết
Xem chi tiết
qwerty
Xem chi tiết
Võ Đông Anh Tuấn
24 tháng 9 2016 lúc 10:10

a ) \(\left(-\frac{40}{51}.0,32.\frac{17}{20}\right):\frac{64}{75}\)

\(=\left(-\frac{40}{51}.\frac{8}{25}.\frac{17}{20}\right):\frac{64}{75}\)

\(=\left(\frac{-40.8.17}{51.25.20}\right):\frac{64}{75}\)

\(=\left(\frac{-16}{75}\right).\frac{75}{64}\)

\(=\frac{-1}{1}.\frac{1}{4}=-\frac{1}{4}\)

 

 

 

qwerty
24 tháng 9 2016 lúc 10:39

giúp nốt

 

Lê Vân Anh
Xem chi tiết
hoanganh nguyenthi
29 tháng 7 2018 lúc 11:03

A)  7/38 x 9/11 +7/38 x 4/11 -7/38 x 2/11

=7/38.(9/11+4/11-2/11)

=7/38

B) 5/31 x 21/25 + 5/31 x -7/10 - 5/31 x 9/20

=5/31.(21/25-7/10-9/20)

=5/31.(-31/100)

=-1/20

Đỗ Thị Hạnh
Xem chi tiết
Chi Lê
Xem chi tiết
Gia Phát
22 tháng 8 2019 lúc 8:04

lớp 1 mà cậu

Rinu
22 tháng 8 2019 lúc 9:13

4.24.52-(33.18+33.12)

=4.24.25-[27.(18+12)]

=(4.25).24-[27.30]

=100.24-810

=2400-810

=1590

кαвαиє ѕнιяσ
8 tháng 6 2021 lúc 21:05

4.24.5^2-(3^3.18+3^3.12)

31.15.7^2.4-31.49.40

1+2+3+4+5+6+7+8+9+10

1+3+5+7+9+11+13+15+19

2+6+10+14+22+23+26+34

5+8+11+14+17+20+23+26+29

1+6+11+16+21+26+31+36+41+47+51

10+13+16+19+22+25+28+31+34+37+40

5+7+9+11+13+15+17+3+8+13+18+23+28

4+7+10+13+16+19+5+9+13+17+21+25 = 1590

#HT#

Khách vãng lai đã xóa
huongff2k3
Xem chi tiết
Nguyễn Văn Nam Hải
29 tháng 3 lúc 9:34

a)\(\dfrac{-10}{11}.\dfrac{8}{9}+\dfrac{7}{18}.\dfrac{10}{11}\)

=\(\dfrac{10}{11}.\dfrac{-8}{9}+\dfrac{7}{18}.\dfrac{10}{11}\)

=\(\dfrac{10}{11}(\dfrac{-8}{9}+\dfrac{7}{18})\)

=\(\dfrac{10}{11}.\dfrac{-1}{2}\)

=\(\dfrac{-5}{11}\)

b; 

B = \(\dfrac{3}{14}\) : \(\dfrac{1}{28}\) - \(\dfrac{13}{21}\)\(\dfrac{1}{28}\) + \(\dfrac{29}{42}\) : \(\dfrac{1}{28}\) - 8

B = (\(\dfrac{3}{14}\) - \(\dfrac{13}{21}\) + \(\dfrac{29}{42}\)) - 8

B = (\(\dfrac{9}{42}\) - \(\dfrac{26}{42}\) + \(\dfrac{29}{42}\)) - 8

B = (\(\dfrac{-17}{42}\) + \(\dfrac{29}{42}\)) - 8

B = \(\dfrac{2}{7}\) - 8

B = \(\dfrac{2}{7}-\dfrac{56}{7}\)

B = - \(\dfrac{54}{7}\)

c; C = -1\(\dfrac{5}{7}\).15 + \(\dfrac{2}{7}\)(-15) + (-105).(\(\dfrac{2}{3}\) - \(\dfrac{4}{5}\) + \(\dfrac{1}{7}\))

C = - 15.(- 1 - \(\dfrac{5}{7}\) + \(\dfrac{2}{7}\) + \(\dfrac{14}{3}\) - \(\dfrac{28}{5}\) + \(1\))

C = -15.[(1 - 1) - (\(\dfrac{5}{7}\) - \(\dfrac{2}{7}\)) + \(\dfrac{14}{3}\) - \(\dfrac{28}{5}\)]

C = -15.[0 - \(\dfrac{3}{7}\) + \(\dfrac{14}{3}\) - \(\dfrac{28}{5}\)]

C = -15 . [- \(\dfrac{45}{105}\) + \(\dfrac{490}{105}\)  - \(\dfrac{588}{105}\)]

C = -15. [ \(\dfrac{445}{105}\) - \(\dfrac{588}{105}\)]

C = - 15.(- \(\dfrac{143}{105}\))

C = \(\dfrac{143}{7}\)